Case Report: Heterozygous Germline Variant in EIF6 Additional to Biallelic SBDS Pathogenic Variants in a Patient With Ribosomopathy Shwachman–Diamond Syndrome - Taha, Ibrahim; Foroni, Selena; Valli, Roberto; Frattini, Annalisa; Roccia, Pamela; Porta, Giovanni; Zecca, Marco; Bergami, Elena; Cipolli, Marco; Pasquali, Francesco; Danesino, Cesare; Scotti, Claudia; et al. (Frontiers in Genetics, 2022)
Background: Shwachman–Diamond syndrome (SDS) is a rare autosomal recessive ribosomopathy mainly characterized by exocrine pancreatic insufficiency, skeletal alterations, neutropenia, and a relevant risk of hematological transformation. At least 90% of SDS patients have pathogenic variants in SBDS, the first gene associated with the disease with very low allelic heterogeneity; three variants, derived from events of genetic conversion between SBDS and its pseudogene, SBDSP1, provided the alleles observed in about 62% of SDS patients. Methods: We performed a reanalysis of the available WES files of a group of SDS patients with biallelic SBDS pathogenic variants, studying the results by next bioinformatic and protein structural analysis. Parallelly, careful clinical attention was given to the patient focused in this study. Results: We found and confirmed in one SDS patient a germline heterozygous missense variant (c.100T>C; p.Phe34Leu) in the EIF6 gene. This variant, inherited from his mother, has a very low frequency, and it is predicted as pathogenic, according to several in silico prediction tools. The protein structural analysis also envisages the variant could reduce the binding to the nascent 60S ribosomal. Conclusion: This study focused on the hypothesis that the EIF6 germline variant mimics the effect of somatic deletions of chromosome 20, always including the locus of this gene, and similarly may rescue the ribosomal stress and ribosomal dysfunction due to SBDS mutations. It is likely that this rescue may contribute to the stable and not severe hematological status of the proband, but a definite answer on the role of this EIF6 variant can be obtained only by adding a functional layer of evidence. In the future, these results are likely to be useful for selected cases in personalized medicine and therapy.